Writing development: A case study of the development of a second language speaker’s academic literacy - Zhang, Xia; Badger, Richard (UNIB Press, 2024)
A major challenge for second language learners on academic programmes is how they develop their writing abilities. This study uses the framework of process writing (Flower & Hayes, 1981; Hayes, 2012) and an autoethnographic research design data construction (Starfield, 2020; Yazan et al., 2020) to explore how one-second language learner changed how they planned their assignments and responded to feedback from their tutors on a one-year MA programme. Working with a critical friend, the author-researcher draws on six data sets: assignment briefs, guidance provided by lecturers, the author/researcher’s outlines/plans for the assignments with comments from lecturers, notes on journal articles and textbooks, feedback from lecturers and personal reflections on the writing process. The author/researcher’s development became more sophisticated in locating/ using sources and structuring her writing with language feedback impacting writing strategies rather than language knowledge. Her writing development was influenced by contextual features, particularly non-academic factors that limited the time she had for writing, and the structure of the assessment on her programme scaffolded her writing in terms of increasing the length of assignments and the use of the author/researcher’s own experience.